Cytotoxicity of 18 Cameroonian medicinal plants against drug sensitive and multi-factorial drug resistant cancer cells. (10th August 2018) - Mbaveng, Armelle T.; Manekeng, Hermione T.; Nguenang, Gaelle S.; Dzotam, Joachim K.; Kuete, Victor; Efferth, Thomas
Abstract: Ethnopharmacological relevance: Recommendations have been made stating that ethnopharmacological usages such as immune and skin disorders, inflammatory, infectious, parasitic and viral diseases should be taken into account if selecting plants for anticancer screening, since these reflect disease states bearing relevance to cancer or cancer-like symptoms. Cameroonian medicinal plants investigated in this work are traditionally used to treat cancer or ailments with relevance to cancer or cancer-like symptoms. Aim of the study: In this study, 21 methanol extracts from 18 Cameroonian medicinal plants were tested in leukemia CCRF-CEM cells, and the best extracts were further tested on a panel of human cancer cell lines, including various multi-drug-resistant (MDR) phenotypes. Mechanistic studies were performed with the three best extracts. Materials and methods: Resazurin reduction assay was used to evaluate cytotoxicity and ferroptotic effects of methanol extracts from different plants. Flow cytometry was used to analyze cell cycle, apoptosis, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) of extracts from Curcuma longa rhizomes (CLR), Lycopersicon esculentum leaves (LEL), and Psidium guajava bark (PGB). Results: In a pre-screening of all extracts, 13 out of 21 (61.9%) had IC50 values below 80 µg/mL. Six of these active extracts displayed IC50 values below 30 µg/mL: Cola pachycarpa leaves (CPL), Curcuma longa rhizomes (CLR), Lycopersicon esculentum leaves, Persea americana bark (PAB), Physalis peruviana twigs (PPT) and Psidium guajava bark (PGB). The best extracts displayed IC50 values from 6.25 µg/mL (against HCT116 p53 -/- ) to 10.29 µg/mL (towards breast adenocarcinoma MDA-MB-231- BCRP cells) for CLR, from 9.64 µg/mL (against breast adenocarcinoma MDA-MB-231 cells) to 57.74 µg/mL (against HepG2 cells) for LEL and from 1.29 µg/mL (towards CEM/ADR5000 cells) to 62.64 µg/mL (towards MDA-MB-231 cells) for PGB. CLR and PGB induced apoptosis in CCRF-CEM cells via caspases activation, MMP depletion and increase ROS production whilst LEL induced apoptosis mediated by caspases activation and increase ROS production. Conclusion: The best botanicals tested were CLR and LEL, which are worth to be explored in more detail to fight cancers including MDR phenotypes. Graphical abstract: Cell cycle distribution of leukemia CCRF-CEM cells treated with bark extract of Curcuma longa rhizomes (CLR), Lycopersicon esculentum leaves (LEL), Psidium guajava bark (PGB) and doxorubicin at their IC50 values for 72 h: Upon treatment, CLR, LEL and PGB induced apoptosis cell cycle arrest in G0/G1 phase whilst doxorubicin induced S and G2/M arrest.